A preliminary investigation of lead poisoning in a Napoleonic era naval cemetery in Antigua, W.I. - Varney, Tamara L.; Swanston, Treena; Coulthard, Ian; Cooper, David M. L.; George, Graham N.; Pickering, Ingrid J.; Murphy, A. Reginald (My University, 2012)
Lead poisoning has been suggested as being partially responsible for the ‘demise’ of the British military in the West Indies during the colonial era. Lead was pervasive in the colonial environment, being employed in items such as eating and cooking utensils, water catchments and alcohol distillation equipment. This preliminary study represents the first attempt to determine whether this suggestion has any validity. A bone sample taken from an individual excavated from a cemetery associated with a Royal Naval Hospital cemetery (c. 1793-1822 C.E.) in Antigua was used for initial testing. A control sample from an individual from a pre-contact site provided baseline/control data. Lead levels and distribution in the samples were mapped by synchrotron microprobe X-ray fluorescence (XRF) at the Stanford Synchrotron Radiation Lightsource (SSRL). Preliminary results revealed that the precontact sample had little to no detectable lead, while that from the historic period did indeed contain lead. Further, within the historic sample, discreet biological structures were found to contain a high level of lead relative to the surrounding bone. This result strongly suggests a biogenic rather than diagenetic origin for the heavy metal. This study marks the first successful application of this technology to archaeological bone samples from this region, and represents an exciting new potential tool for bioarchaeology.
Keywords: colonial West Indies; lead; synchrotron techniques; bioarchaeology